Evaluation of the Performance of the Technical Education and Skills Development Authority (Tesda) Training Institutions in Region VIII - Geryl Cataraja; Roger Cataraja (PT FORMOSA CENDEKIA GLOBAL, 2022)
The main objective of this study was to evaluate the performance of the Technical Education and Skills Development Authority (TESDA) Training Institutions in Region VIII covering the three provinces of Biliran, Leyte, and Eastern Samar. The findings revealed that the overall rating in all the areas of performance resulted to a Level 1 status which means that the three training institutions in Region VIII have met the threshold of APACC standards and their deficiencies could be improved within a period of two years. Based on the documentary inspection of the researcher, the performance level of the training and facilitative staff based on their Performance Evaluation System (PES) was very satisfactory. Furthermore, the results showed that the training and facilitative staff were performing their duties and functions in accordance with their job description. On the relationship between variables it was revealed that the performance of the training and facilitative staff was not significantly related to the performance of the training institutions.Anchored on the findings presented, it was concluded that the performance of the three TESDA Training Institutions have met and qualified on the Level I status which corresponds to the Asia Pacific. Moreover, the performance of the training staff is not related to that of the facilitative staff. However, the performance of the training and facilitative staff is independent on the performance of the training institution.